Private Health : Policy and Regulatory Options for Private Participation - World Bank (Washington, DC, 2012)
Many developing countries face a critical gap between the demand for health care services and their supply. Public resources often fall short of what is needed to provide universal health care, and the typical incentive structure in the public sector may not always be conducive to expanding access, improving the quality of care, and ensuring efficient use of limited funding and expertise. This Note defines options for mobilizing private resources to achieve public health objectives. A government seeking to encourage private participation in health care provision can choose among six basic policy and regulatory options that vary widely in the risks and responsibilities borne by the private (for-profit or nonprofit) entity. At one end of the spectrum the private sector takes on limited responsibilities while the public sector remains the primary provider of health care services. At the other, the government establishes a policy environment in which qualified private entities may freely enter and exit the health care market. In this option private providers assume the full risks and responsibilities associated with service provision, and the public sector limits its role to regulation.